With a beginning? Or eternal? Origins and controversies in cosmology in the middle of the last century - Videira, Antônio Augusto Passos; Vieira, Cássio Leite (Cadernos de Astronomia, 2023)
A few years after the end of World War II, cosmology - a discipline then in search of respectability - was involved in a controversy regarding the question of whether (or not) the universe had an origin. In this article, we review that period, describing the main ideas and names of this unique event.
Keywords: Big Bang; nucleosynthesis; steady state theory; George Gamow; Fred Hoyle